Evolution of Pleistocene travertine depositional system from terraced slop to fissure-ridge in a mixed travertine-alluvial succession (Jebel El Mida, Gafsa, southern Tunisia). Issue 1 (1st January 2017) - Henchiri, Mohsen; Ben Ahmed, Walid; Brogi, Andrea; Alçiçek, Mehmet Cihat; Benassi, Ramdhane
Abstract : The Quaternary stratigraphic record of Jebel El Mida, composed of continental deposits, is a useful example of concomitant travertines and alluvial deposition in an extensional setting. Travertine deposition occurred in a faulted Pleistocene alluvial fan giving rise to seven (recognised) facies interfingering with five other alluvial ones. The travertine depositional events indicate a tectonically driven evolution from terraced slope (facies group FC1–FC6) to a travertine fissure ridge-type depositing phase (facies group of FC1–FC7). Interfingering between travertine and alluvial facies indicates the co-existence of adjacent and time-equivalent depositional environments. The travertine deposition resulted from deep origin hydrothermal fluids channelled along damaged rocks volumes associated to a regional fault system, named as the Gafsa Fault (GF). The travertine–terrigenous succession in Jebel El Mida highlights the major role played by the GF in controlling: (i) the hydrothermal fluid flow, still active as also indicated by the numerous thermal springs aligned along the fault zone; (ii) paleoflow directions, discharge locations, volume, rate and fluctuations of the water supply. The paleoclimatic correlation with adjacent localities reveals that, at that time, humid episodes could have contributed to the recharge of the hydrothermal system and to the deposition of alluvial sediments.